Development in the multiaxis 3D weaving technology. Issue 17 (October 2016) - Labanieh, Ahmad Rashed; Legrand, Xavier; Koncar, Vladan; Soulat, Damien
Multiaxis 3D weaving technology allows insertion of in-plane fibres reinforcements, designated as bias yarns, oriented in directions other than 0° and 90° in the woven preform, unlike in the case of conventional weaving technology. By different existing weaving advanced techniques, two opposite bias yarn layers are formed, with no possibility to separate them by in-plane yarn layer oriented in 0° to reduce inter-layer angle. That could be the cause of weak interlaminar shear resistance in the final composite structure. In this present paper, a novel development is proposed to solve the issues related to the guide block technique, which is used to position the bias yarns in the weaving zone on the weaving loom. Thus, in order to enable insertion of in-plane yarns layer oriented in 0° between the two opposite successive bias yarn layers (±θ°). Furthermore, the proposed technique is upgraded to control the width of produced preform on the loom. The proposed approach has reduced degradations of the in-plane warp and bias yarns during a weaving process caused by the friction with reed blades. Geometrical characterization of manufactured preform, using the developed multiaxis 3D weaving loom prototype, has been carried out to observe the yarn geometry inside the impregnated preform. Similarly, the geometrical properties of the impregnated preform are compared with those of multiaxis 3D woven preforms produced by the tube carrier weaving technique and the tube rapier weaving technique.